Amphiphilic Gemini Pyridinium-mediated incorporation of Zn(II)meso-tetrakis(4-carboxyphenyl)porphyrin into water-soluble gold nanoparticles for photodynamic therapy - Alea-Reyes, María E.; Soriano, Jorge; Mora-Espí, Inma; Rodrigues, Mafalda; Russell, David A.; Barrios, Leonardo; Pérez-García, Lluïsa (Elsevier, 2017)
Zn-containing porphyrins are intensely investigated for their ability to form reactive oxygen species and thereby being potent photosensitizers for use in photodynamic therapy (PDT). Some of the drawbacks of the PDT approach, such as unspecific distribution, could be addressed by means of photosensitizer drug delivery systems. In this work, we synthesize and characterize new water-soluble gold nanoparticles (GNP) stabilized by a mixture of a polyethyleneglycol-containing thiol (to improve water solubility) and a new amphiphilic gemini-type pyridinium salt, which also acts as promotor of the incorporation of the anionic photosensitizer Na-ZnTCPP into the GNP. The obtained GNP have sizes between 7 and 10 nm, as observed by Transmission Electron Microscopy. The incorporation of the photosensitizer caused an increase in the hydrodynamic size, detected by Dynamic Light Scattering, as well as a shift in the Surface Plasmon Resonance peak on the GNP UV–vis absorption spectra. The presence of the photosensitizer in the GNP was corroborated using Fluorescence Spectroscopy. The amount of Na-ZnTCPP was found to be 327 molecules per GNP. The porphyrin-containing Na-ZnTCPP-1·GNP showed good enhanced ability to produce singlet oxygen, compared to free Na-ZnTCPP. Their cytotoxicity and phototoxicity were investigated in vitro using two different human breast cell lines, one of tumoral origin (SKBR-3) and another of normal epithelium origin (MCF-10A). SKBR-3 cells showed higher sensitivity to Na-ZnTCCP and Na-ZnTCPP-1·GNP in dark conditions. After irradiation, no significant differences were observed between both cell lines except for 1 μM Na-ZnTCCP-1·GNP where SKBR-3 cells were also more sensitive.